Pengaruh Implementasi Program Sekolah Penggerak Terhadap Hasil Belajar Matematika Siswa Kelas XI SMA Negeri 4 Baubau - Alfin Alfin; Suwarni La Usa; Artati Iriana (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2026)
The problem in this study is, is there any significant effect of the implementation of the Sekolah Penggerak program on the learning outcomes of class XI students of SMA Negeri 4 Baubau?. The purpose of the study was to determine the effect of the implementation of the Sekolah Penggerak program on the mathematics teaming outcomes of class XI students of SMA Negeri 4 Baubau.This research is included in the type of quantitative research with the Espost Facto approach. The population in this study were all students of class XI of SMA Negeri 4 Baubau in the 2024/2025 Academic Year consisting of 6 parallel classes, namely 145 students. The sampling technique used was Simple Random Sampling using the slovin formula. While the sample in this study. as much as 74, of the population of 6 classes, namely 106 students. The instruments in this study were questionnaires and students' mathematics learning outcomes. The data collection technique used was by administering a questionnaire manually (offline) and taking students' mathematics learning outcomes obtained from report card scores on the knowledge aspect of mathematics subjects for class XI students of SMA Negeri 4 Baubau in the odd semester of the 2023/2024 academic year. The data analysis was carried out using Simple Linear Regression analysis. Based on the results of the analysis using simple regression. the linear regression equation is obtained: Y = 23.816 + 0.678X. With a t value of 9.518, significant at 0.000 < 0.05. This shows that H1 is accepted and H0 is rejected. This means that the implementation of the Sekolah Penggerak program has a significant effect on the mathematics teaming outcomes of class XI students of SMA Negeri 4 Baubau.